Distribution and Abundance of Marine Debris Along the Coast of Karachi (Arabian Sea), Pakistan: Marine Debris Along the Karachi Coast - Qari, Rashida; Shaffat, Moniba (Biological Sciences - PJSIR, 2015)
This study reports the first assessment of distribution and abundance of marine debris along the coast of Karachi (Arabian Sea), Pakistan. The quadrate method was used for estimating the debris material. Total 40 quadrates were made for collecting the debris on 4 beaches: Sandspit, Buleji, Paradise Point and Korangi Creek in the year of 2012. Nine different types of debris comprising of plastics, glasses, thermopore, clothing, rubber, paper, pot pieces and cigarette filters were collected. The study revealed that, plastic was found in high quantity at all four beaches of Karachi. Other most common items were as follow: plastic at Paradise Point and Sandspit; pot pieces at Korangi Creek and rubber at Buleji. A total weight of 12277.45 g debris was recorded during the whole study period. It was also noted that Paradise Point is the dirtiest beach (5612.6 g) when compared with other studied beaches.